DEVELOPMENT OF MULTIMEDIA-DIGITAL IN EARLY CHILDREN LEARNING AT PAUD AL-IRSYAD AL ISLAMIYAH JEMBER - Yeni Rofiah; Nurul Anam (International Conference on Humanity Education and Society (ICHES), 2023)
Digital multimedia is an important learning component. The current educational process should take advantage of multimedia-digital technology which has developed a lot in the world of education. The institute of PAUD Al-Irsyad Al Islamiyyah Jember strive to make this happen Therefore, the purpose of this study was to determine the development of digital multimedia in early childhood learning on the theme " Nutrition Guide for Balanced Diet" at Early Childhood Education, Al Irsyad Al Islamiyyah Jember 2021/2022. This research method uses R&D and the development model uses the ASSURE Model. Methods of data collection using questionnaires, observation, interviews, and documentation. The data analysis uses statistical analysis and Miles & Huberman. The results of his research show that this digital-multimedia development stage includes the process of analyzing the characteristics of students; determine KD (Basic Competence); choosing media, teaching materials and methods; designing and using media and learning materials in IT media; involving students in the learning process that uses the theme media "Nutrition Guide for Balanced Diet"; and evaluating and revising the developed "Nutrition Guide for Balanced Diet" Theme media products.